A neural system dynamics modeling platform and its applications in randomized controlled trial data analysis. (2021) - Hamid, Nadira; Sarkar, Joydeep; Redfors, Bjorn; Balani, Anisha; Ramaswamy, Rajagopalan; Ghosh, Abhijit; Alu, Maria; Crowley, Aaron; Zhang, Yiran; Leon, Martin B.; Stone, Gregg W.; Granada, Juan F.
Abstract: Background: Conventional statistical methods used in clinical trials lack the ability to predict patient specific risk and very often do not consider the effects of time varying interventions. The aim of this study is to test a novel artificial neural network based model for clinical trial analysis to represent the continuous time evolution of risk. Methods: The novel methodology tested utilizes system dynamics and artificial neural networks. This methodology was applied to analyze data from 2, 221 patients with acute myocardial infarction enrolled in a well characterized randomized study, the HORIZONS-AMI trial. Outcomes analyzed included: (1) target lesion revascularization (TLR) and (2) stent thrombosis. The proposed neural system dynamics (NSD) model was compared against traditional Cox Proportional Hazards (Cox PH) and Cox neural network (NN) models. Model performance was evaluated using C-statistic at 1, 2 -and 3- years follow-up and model-based simulation studies were performed to examine the effect of different variables on the predicted risk of TLR and stent thrombosis. Results: The NSD model achieved comparable performance to Cox models for TLR. For stent thrombosis, the NSD model outperformed Cox models (1-year C-statistic: Stent thrombosis – Cox PH: 0.60, Cox NN: 0.66, neural SD model: 0.69). The neural SD model identified clinically relevant variables such as stent count, stent type and multiple lesions treated as significant predictors for TLR; and stent count and peak platelet count for stent thrombosis. Simulations illustrated change in predicted TLR risk maximal for the neural SD model, compared to other models. For stent thrombosis, simulation scenario illustrated predicted event rate doubling when clopidogrel is discontinued at 6 months compared to extended use. Conclusions: We have demonstrated an alternative analytical methodology that combines system dynamics and artificial neural networks to analyze results from a randomized trial. This novel approach can incorporate patient-specific longitudinal data and provide personalized risk prediction. Highlights: Incorporation of non-linear interactions and time-varying data improves personalized risk prediction. Neural System Dynamics (NSD) model combines neural networks with system dynamics. NSD model represents continuous time evolution of risk. NSD model captures clinically relevant risk predictors of Target Lesion Revascularization and Stent Thrombosis. NSD model based simulations provide more personalized risk trajectories with actionable insights using follow-up intervention information.